A review of the literature on leadership in early childhood: examining epistemological foundations and considerations of social justice. Issue 2 (25th January 2020) - Nicholson, Julie; Kuhl, Katie; Maniates, Helen; Lin, Betty; Bonetti, Sara
ABSTRACT: With the increasing acknowledgement of the benefits of early childhood education, there is a need to ask critical questions about whether ample leadership exists for guiding ambitious systemic change in the field. This review of leadership in early childhood educational contexts between 1995 and 2015 examines the epistemological assumptions embedded in the literature (and those advantaged and marginalized as a result), the expressed purposes of leadership work and specifically, whether, and to what extent, considerations of social justice and equity have been included in leadership theorizing. Eighty-one publications were identified through a search of major electronic databases and analysed using an analytic review template that includes definitions of leadership, modern and postmodern epistemologies underlying these texts, and considerations of social justice. Findings suggest that while traditional hierarchical conceptions are common, there is a shift towards more distributed and relational understandings of leadership. More recently, leadership is being described as a socially constructed, situated, culturally informed and dynamic process. There has also been an increase in the number of scholars emphasizing postmodern thinking in discussions of leadership over modernist conceptions. Still, there is less explicit discussion of postmodern intersectional identities in leadership. In addition, most literature does not include explicit discussion of social justice in theorizing about leadership, or the expressed purposes of leadership. This suggests the importance of critically examining the epistemological assumptions represented in leadership discourse and of more intentional links between leadership and goals that address social injustices for children, families and the early childhood workforce.